Atividade antimicrobiana, antibiofilme e citotoxicidade do óleo essencial de Thymus vulgaris com ênfase em biofilmes de Pseudomonas aeruginosa - Rockenbach, Andressa Ester (2023)
Biofilms are characterized as a set of microorganisms surrounded by a matrix of extracellular polysaccharides. Pseudomonas aeruginosa is a Gram negative bacillus, which expresses several virulence factors. The ability of these microorganisms to form biofilms has significantly increased resistance to existing drugs, making treatment difficult. Thus, new alternatives to combat these infections are urgent, and in this context, essential oils have been studied for their broad antimicrobial action. The essential oil of Thymus vulgaris has been demonstrating action against several microorganisms, and can be considered promising in the fight against biofilms. The aim of this study was to evaluate the antimicrobial, antibiofilm and cytotoxicity of T. vulgaris essential oil, with emphasis on P. aeruginosa biofilms (Pa01). The following microorganisms were used: P. aeruginosa (Pa01), Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Klebsiella pneumoniae (ATCC 700603), Shiguella flexneri (ATCC 12022323A), Enterococcus faecalis (ATCC 51299) and Streptococcus mutans (ATCC 25175). The essential oil of T. vulgaris was characterized by gas chromatography, and the antimicrobial activity was performed by the disk-diffusion and microdilution methods, to determine the minimum inhibitory and bactericidal concentration. The antibiofilm activity was determined through the crystal violet assay, the count of viable colonies in the formed biofilm and the kinetics of the biofilm in relation to time. The influence on swimming, swarming and twitching motilities of P. aeruginosa was also evaluated using specific culture media. Cytogenotoxicity of the oil was evaluated in three healthy cell lines. The characterization of the oil showed thymol (41.8%) and paracymene (31.6%) as major components. The oil showed antimicrobial and antibiofilm activity against all tested bacteria. In relation to the Pa01 strain, the results showed that the oil is capable of inhibiting and destroying the formed biofilm significantly and quickly, as shown by the kinetics in relation to time, in addition to having shown influence on swimming, swarming and twitching motility. At the tested concentrations (2,5 mg/mL, 5 mg/mL and 10 mg/mL), the oil showed cytotoxicity in the three cell lines used. The present study demonstrated that the essential oil of T. vulgaris has great antimicrobial and antibiofilm potential, but further studies are needed to seek alternatives to reduce the cytotoxicity presented, so that it can be used as a pharmacological strategy.